2018
DOI: 10.1149/2.0181809jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Zinc from 1-ethyl-3-methylimidazolium acetate-water Mixtures: Investigations on the Applicability of the Electrolyte for Zn-Air Batteries

Abstract: In this paper, the influence of various concentrations of water on the electrochemical and spectroscopic behavior of 1-ethyl-3methylimidazolium acetate ([EMIm]OAc) and of 1 M Zn(OAc) 2 /[EMIm]OAc has been investigated. The results show that the added water can reduce the viscosity and improve the conductivity of the employed electrolyte. Spectroscopy results reveal that both [EMIm]OAc and 1 M Zn(OAc) 2 /[EMIm]OAc interact with water and the extent of interaction varies with the amount of water. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 62 publications
0
20
0
1
Order By: Relevance
“…There are already a number of studies on the influence of water on the Zn deposition and dissolution behavior in various ILs, focusing mostly on the effect of water on the morphology of the resulting deposits, but also dealing with the reaction rate and the reversibility of the Zn redox couple. 15,[17][18][19][20] More specifically, for BMP-TFSI Xu et al concluded that on Pt electrodes the redox reversibility of the Zn/Zn(II) redox couple is improved and the reaction rate is increased upon addition of water. 17 At (too) high water levels this leads to a decrease of the electrochemical stability window.…”
mentioning
confidence: 99%
“…There are already a number of studies on the influence of water on the Zn deposition and dissolution behavior in various ILs, focusing mostly on the effect of water on the morphology of the resulting deposits, but also dealing with the reaction rate and the reversibility of the Zn redox couple. 15,[17][18][19][20] More specifically, for BMP-TFSI Xu et al concluded that on Pt electrodes the redox reversibility of the Zn/Zn(II) redox couple is improved and the reaction rate is increased upon addition of water. 17 At (too) high water levels this leads to a decrease of the electrochemical stability window.…”
mentioning
confidence: 99%
“…Organic weak acids, like carboxylic or aminocarboxylic acids, and their salts have been studied for many years as additives to aqueous zinc electrolytes to improve the quality of Zn deposition and suppress the HER . These acids are often polyprotic, the conjugate bases are negatively charged, and they can be combined with a positive counter‐ion.…”
Section: Electrolyte Design Methodsmentioning
confidence: 99%
“…Organic weak acids, like carboxylic or aminocarboxylic acids, and their salts have been studied for many years as additives to aqueous zinc electrolytes to improve the quality of Zn deposition and suppress the HER. [30,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] These acids are often polyprotic, the conjugate bases are negatively charged, and they can be combined with a positive counter-ion. The solubilities of zinc-organic salts are usually high enough so as not to threaten the precipitation of ZnO.…”
Section: Electrolyte Componentsmentioning
confidence: 99%
“…The adsorption isotherms of EMIM Ac and the ionogel were type III with a characteristic linear uptake at low vapor concentrations (below 50% RH) and a strong increase in adsorption at higher vapor concentrations (above 50% RH). At a lower RH, the hydroxyl group of water preferentially interacted with the carbonyl group of the anionic part of EMIM Ac [61]. These adsorbed water vapor molecules then acted as secondary sites for further water adsorption, and hydrogen bonds between water vapor molecules formed at a higher RH.…”
Section: Adsorption Capacitymentioning
confidence: 99%